Implementasi Kebijakan Pengelolaan Dana Desa di Desa Tumbang Tarusan Kecamatan Tewang Sangalang Garing Kabupaten Katingan: Implementation of Village Fund Management Policies in Tumbang Tarusan Village, Tewang Sangalang Garing District, Katingan Regency - Ratmoko, Ambar; Anugrah, Yahya (Pencerah Publik, 2016)
The purpose of this study was to determine the Implementation of Village Fund Management Policies in Desatumbang Tarusan, Tewang Sangalang Garing District, Katingan District. This study uses qualitative research. The data source consists of primary sources. Techniques for collecting data by observation, interviews, and documentation. Research Results Implementation of Village Fund Management Policies in Desatumbang Tarusan, Tewang Sangalang Garing District, Katingan Regency, Based on the results of research and discussion on the Implementation of Village Fund Management Policies in Tumbang Tarusan Village, Tewang Sangalang Garing Subdistrict, Katingan District based on 4 indicators: Communication, Resources, Disposition and Bureaucratic Structure It can be concluded that the Implementation of Village Fund Policy in Tumbang Tarusan Village, Tewang District, Sangalang Garing, is said to have not been successful. This is because of the 4 indicators that measure the success of the implementation, only one indicator shows a success, that is, power. While Communication, Disposition, and Bureaucratic Structure are still not going well.